Investing in Resource Efficiency The Economics and Politics of Financing the Resource Transition (Springer International Publishing, 2018)
This book covers the multi-faceted incentives, trade-offs, and challenges associated with the economics and politics of resource efficiency investments. By contributing a wide range of empirical evidence, practitioners' insights, and policy perspectives, this book carefully examines the role of resource efficiency in reconciling environmental and economic considerations. It also discusses the critical role of resource efficiency investments in mitigating climate change and enabling sustainable development. Featuring expert insights from academia, the European Commission, the European Investment Bank, and the European Bank for Reconstruction and Development, this book provides a policy oriented guide, reference, and toolbox for unlocking the potential of resource efficiency. To this end, it identifies practical measures for overcoming barriers and creating smart incentives for leveraging resource efficiency investments. Overall, this book brings together evidence to develop innovative ideas and strategies for improving the efficient use of resources and advancing clean and sustainable development. "This book is an important and timely contribution", Angel Gurria, Secrectary General, OECD.